2011
DOI: 10.1093/cid/cir729
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Criteria Are Poor Predictors of Virologic Outcome: Implications for HIV Treatment Monitoring in Resource-Limited Settings

Abstract: Because of the low sensitivity of immunologic criteria, a substantial number of failures are missed, potentially resulting in accumulation of resistance mutations. In addition, specificity and predictive values are low, which may result in large numbers of unnecessary ART switches. Monitoring solely by immunologic criteria may result in increased costs because of excess switches to more expensive ART and development of drug-resistant virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
108
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 27 publications
9
108
1
2
Order By: Relevance
“…In our study, some of the patients who responded to therapy using clinical parameters only were already failing virologically. Other reports have suggested similar findings in resource-poor settings [20]. Similar to our study findings, these reports show that clinical criteria are poor predictors for virological outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, some of the patients who responded to therapy using clinical parameters only were already failing virologically. Other reports have suggested similar findings in resource-poor settings [20]. Similar to our study findings, these reports show that clinical criteria are poor predictors for virological outcome.…”
Section: Discussionsupporting
confidence: 92%
“…In Tanzania, Muhimbili Hospital started to provide ART earlier than many other centers. It has been demonstrated that virological failure, both in terms of insufficient suppression of viral load, and in terms of drug resistance, precedes CD4 cell decline, which ultimately leads to clinical progression and death [20]. To follow up patients using clinical parameters, thus, means that any therapy change will be delayed compared to following up using virological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In resource-limited settings, WHO recommends monitoring and detection of treatment failure using a four-stage classification system for clinical symptoms and immunological assessment with CD4 monitoring (2). However, substantial misclassification of treatment failure may occur when using only these WHO criteria, potentially leading to both treatment regimen changes and accumulation of drug resistance mutations (3,4). Therefore, for proper disease monitoring and clinical management, accurate quantification of HIV-1 RNA using PCR-based assays is essential.…”
mentioning
confidence: 99%
“…(5) which found that immunological criteria has poor prediction of virological failure. The study showed the sensitivity of immunological criteria to detect viral failure was 58%, specificity was 75% and the positive-predictive value was 39%.…”
Section: Discussionmentioning
confidence: 99%